Multi-stakeholder perspectives on reproductive and adolescent healthcare schemes in tribal regions of India: A qualitative study - Rohit Raj; Jarina Begum; Syed Irfan Ali; Manasee Panda (PLoS ONE, 2026)
Tribal populations, comprising 8.9% of India’s population, remain highly vulnerable to poor health outcomes due to socioeconomic deprivation, cultural barriers, and limited access to healthcare. Tribal women are disproportionately affected, facing high maternal mortality, poor reproductive health, and inadequate nutrition. Although government schemes such as Janani Suraksha Yojana (JSY) and Rashtriya Kishori Swasthya Karyakram (RKSK) aim to improve outcomes, utilization remains low. This study explored challenges and enablers in reproductive healthcare provision from multiple stakeholder perspectives in tribal Jharkhand. A descriptive qualitative study was conducted from December 2024 to June 2025 in two blocks of East Singhbhum district, Jharkhand. Using purposive sampling, 38 in-depth interviews were undertaken with stakeholders including tribal women, adolescent girls, Accredited Social Health Activists (ASHAs), Auxiliary Nurse Midwives (ANMs), Anganwadi Workers (AWWs), medical officers, and village heads. Interviews were conducted in Hindi, audio-recorded, translated, and transcribed into English. Thematic analysis was performed using Atlas.ti (version 8). Key challenges reported from the framed nine categories. Absenteeism of healthcare workers, inadequate infrastructure, cultural reliance on traditional medicine, weak governance, delayed incentive payments, financial and transport barriers, and limited awareness and use of health technology were the important themes developed. Enabling themes included supervision by higher authorities, quality service delivery, support from community leaders, and collaborations with NGOs. Significant barriers persist in delivering reproductive health schemes in tribal Jharkhand. Strengthening governance, ensuring workforce accountability, improving infrastructure, timely incentives, and implementing culturally tailored awareness interventions are essential to enhance reproductive health outcomes among tribal women and adolescents. Trial Registration: This study is registered at Clinical Trial Registry-India (CTRI) with CTRI No: CTRI/2024/03/063824 on March 8, 2024.